The Effect of Birthball Exercise to Reduce Pain During the First Stage of Labor - Az-zahrah, Mulia; Ferina, Ferina; Sriwenda, Djudju (PROMOTOR, 2025)
Background: Labor is a significant moment that often causes anxiety and pain in women. This pain results from cervical dilation, uterine contractions, and nerve compression. It typically occurs during the first stage of labor with varying intensity: discomfort at 0-3 cm dilation, sharp pain at 4-7 cm, and severe pain at 7-10 cm. Research by Maslikhanah (2020) indicates that 60% of primiparas and 45% of multiparas report severe pain. Labor pain can prolong the process if not managed properly. To address this, pain management techniques such as birthball exercise are recommended during the first stage of labor. Objective: To determine the effect of Birthball Exercise on reducing pain during the first stage of labor. Method:  The method used involves searching for articles using electronic databases like Google Scholar and PUBMED, with publications from the past 5 years, and keywords including birthball exercise, labor pain, and first stage of labor. Results: There is a reduction in labor pain scores following the implementation of the Birthball Exercise method. Conclusions: Implementing birthball exercise during the first stage of labor can help reduce the intensity of labor pain.